Współczesne problemy i praktyka kształcenia matematycznego studentów - Pardała, Antoni (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
The subject matter of this paper relates to one of the modern research trends in teaching mathematics: the problems of quality of mathematical education of pupils and students in the twenty-first century in different countries and cultural traditions. This analysis throws light on the literature, research results, and observations from the Polish perspective of practice, and outlines the intentions of the range. The work also discusses some theoretical bases for the concept of improving the quality of mathematics and its determinants, as well as new ideas and trends, experiences and difficulties related to the implementations made in this respect in Poland. The author of the paper points out the challenges of work, and current areas of research on improving the quality of education, focusing on math problems and methodologies for monitoring and diagnosing the quality of mathematical education of students, and for designing and implementing the practice of teaching online course in mathematics and mathematical subjects.